2006
DOI: 10.1254/jphs.fp0060021
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Induces Vasoconstriction Through the Phosphatidylinositol 3-Kinase-Mediated Mitogen-Activated Protein Kinase Pathway in Hypertensive Rats

Abstract: Abstract. We investigated whether increased contractile responsiveness to epidermal growth factor (EGF) is associated with altered activation of mitogen-activated protein kinase (MAPK) in the aortic smooth muscle of deoxycorticosterone acetate (DOCA)-salt hypertensive rats. EGF induced contraction and MAPK activity in aortic smooth muscle strips, which were significantly increased in tissues from the DOCA-salt hypertensive rats compared with those from shamoperated rats. AG1478, PD98059, and LY294002, inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…In contrast, we found that the activity of Syk, but not that of Akt, in the resting state, was greater in cells from hypertensive rats compared with cells from normotensive rats. Previously, we reported that the PI3K-related MAPK pathway was increased in vascular smooth muscle in hypertensive rats and this was correlated with increases in vascular responses [40, 41]. These results suggest that the altered vascular responses to sVCAM-1 in hypertension can come from the hypertension-associated increase in plasma levels of VCAM-1 or intracellular signal transmission in smooth muscle cells, but not the expression of VLA-4α receptor.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, we found that the activity of Syk, but not that of Akt, in the resting state, was greater in cells from hypertensive rats compared with cells from normotensive rats. Previously, we reported that the PI3K-related MAPK pathway was increased in vascular smooth muscle in hypertensive rats and this was correlated with increases in vascular responses [40, 41]. These results suggest that the altered vascular responses to sVCAM-1 in hypertension can come from the hypertension-associated increase in plasma levels of VCAM-1 or intracellular signal transmission in smooth muscle cells, but not the expression of VLA-4α receptor.…”
Section: Discussionmentioning
confidence: 69%
“…Increased MMP activity, HB-EGF shedding, and EGFR activation have been linked to vasoconstriction caused by G protein-coupled receptor agonists phenylephrine and endothelin-1 (7,16) and increased intravascular pressure (31). In addition, exogenous HB-EGF caused constriction of rat mesenteric arteries (16), and EGF-induced contraction was greatly enhanced in aorta isolated from hypertensive rats (14,26). Our present findings are also consistent with our previous work demonstrating that OxyHb-induced vasoconstriction of smalldiameter cerebral arteries involves tyrosine kinase activation leading to K V channel internalization (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mineralocorticoid deoxycorticosterone acetate (DOCA) can also lead to changes in vascular function with increased basal tone and EGF-induced contraction in hypertensive DOCA-salt rats. Inhibition of PI3kinase and the use of the EGFR kinase inhibitor AG1478 suppressed these alterations in the vasculature [28]. Additionally, an increase in EGFR-mRNA levels accompanied by an EGFinduced arterial contraction has been reported in hypertensive rats [29,30].…”
Section: Physiological Effectsmentioning
confidence: 95%